The Jurisdiction Of The Religious Courts Over Islamic Banking Disputes In Indonesia - St Salehah Madjid; Ulil Amri; Pantja Nurwahidin; Nurmi Nurmi; Shokhrud Fayziev (Universitas Muhammadiyah Makassar, 2025)
The settlement of Islamic economic disputes, particularly those related to Islamic banking, falls under the jurisdiction of the Religious Courts in Indonesia. This study examines two main issues: the scope of the Religious Courts’ authority in resolving Islamic banking disputes and their readiness in terms of institutional structure, legal politics, and substantive law. The research aims to analyze the legal foundation of such authority and to assess the institutional and normative preparedness of the Religious Courts in handling Islamic banking disputes. This study employs a descriptive qualitative method with a normative–conceptual approach, using primary data derived from statutory regulations, legal documents, and relevant legal literature. The findings indicate that the absolute jurisdiction of the Religious Courts is expressly regulated in Article 49 of Law No. 3 of 2006, which authorizes these courts to examine, adjudicate, and resolve disputes among Muslims, including those arising from Islamic economic transactions. Furthermore, the readiness of the Religious Courts in resolving Islamic banking disputes encompasses three key aspects: the professionalism and legal competence of judges and court officials; the understanding of legal politics to harmonize the Islamic banking legal system with the conventional banking framework while upholding Islamic legal principles; and the strengthening of legal substance through the enactment of statutory regulations and the development of the Compilation of Islamic Economic Law (Kompilasi Hukum Ekonomi Syariah/KHES). These elements are essential to ensure effective and legally sound dispute resolution within the Religious Court system.